DETERMINATION OF EMPLOYEE PERFORMANCE: PERCEIVED ORGANIZATIONAL SUPPORT, COMMUNICATION, AND LEADERSHIP STYLES (A HUMAN RESOURCE MANAGEMENT LITERATURE STUDY) - Hazrati Havidz, Hazimi Bimaruci; Gupron, Gupron (Dinasti International Journal of Digital Business Management, 2019)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomenon of the relationship or influence between variables. This article reviews the factors that influence organizational commitment and employee performance, namely: Perceived Organizational Support, Communication, and Leadership Style, a Human Resource Management Literature Study. The results of this research library are that: 1) Perceived Organizational Support has an effect on Employee Performance; 2) Communication has an effect on employee performance; 3) Leadership Style affects Employee Performance.